1969
DOI: 10.1111/j.1469-8986.1969.tb02887.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Evoked Potentials to Semantic Stimuli

Abstract: The influence of affective meaning on the photically evoked response was studied in male college students. Three sets of stimuli were used: taboo words, neutral words, and blank flashes. Two blocks of trials were run for each stimulus, one in which the S responded by calling the stimulus presented, and a second in which the S was not required to respond. The late components of the evoked potential were significantly related to both the stimulus and response conditions. Amplitude 2 was larger for the taboo word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Other studies report even earlier emotionality-dependent modulations of ERPs before or around 200 ms with particular task designs such as near-subliminal (Begleiter and Platz, 1969; Bernat et al, 2001; Ortigue et al, 2004) or hemifield presentation of words (Schapkin et al, 2000; Landis, 2006; Kanske and Kotz, 2007). Across input modalities (words, pictures, videos) emotional stimuli have shown a processing advantage over neutral ones (Eviatar and Zaidel, 1991; Dijksterhuis and Aarts, 2003), characterized at the neural level with amplified cortical responses (Cahill et al, 1996; Hamann et al, 1999; Herbert et al, 2009; Hofmann et al, 2009; Schacht and Sommer, 2009a,b), which is explained by the intrinsic relevance and salience of emotional stimuli (Lang et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Other studies report even earlier emotionality-dependent modulations of ERPs before or around 200 ms with particular task designs such as near-subliminal (Begleiter and Platz, 1969; Bernat et al, 2001; Ortigue et al, 2004) or hemifield presentation of words (Schapkin et al, 2000; Landis, 2006; Kanske and Kotz, 2007). Across input modalities (words, pictures, videos) emotional stimuli have shown a processing advantage over neutral ones (Eviatar and Zaidel, 1991; Dijksterhuis and Aarts, 2003), characterized at the neural level with amplified cortical responses (Cahill et al, 1996; Hamann et al, 1999; Herbert et al, 2009; Hofmann et al, 2009; Schacht and Sommer, 2009a,b), which is explained by the intrinsic relevance and salience of emotional stimuli (Lang et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Thus far it is not entirely clear as to whether we are dealing with subconscious reactions to emotionally significant words or whether the subjects are reluctant to respond when an "unpleasant" word appears on the screen (Whittaker et al, 1952). The fact that the need to respond verbally is not indifferent to the subject is indicated by the experiments of Begleiter and Platz (1969). Retarded components of potentials elicited by "forbidden" words were expressed more strongly than those elicited by neutral words.…”
Section: Effect Of Emotions On Activity (Using the Processes Of Percementioning
confidence: 99%
“…First, P2 was related to attention and categorization around 150–300 ms post-stimulus onset (Antal et al, 2001; Crowley and Colrain, 2004). Second, a plethora of research has found that emotional effect takes place in the P2 time-window in visible conditions (Begleiter and Platz, 1969; Begleiter et al, 1979; Williamson et al, 1991; Schapkin et al, 2000; Ortigue et al, 2004; Kanske and Kotz, 2007; Wang and Bastiaansen, 2014). For instance, Herbert et al (2006) observed that negative words elicited larger P2 component compared with neutral words.…”
Section: Introductionmentioning
confidence: 99%